A global model of cylindrical and coaxial surface-wave discharges. (25th May 2017) - Kemaneci, Efe; Mitschker, Felix; Rudolph, Marcel; Szeremley, Daniel; Eremin, Denis; Awakowicz, Peter; Peter Brinkmann, Ralf
Abstract: A volume-averaged global model is developed to investigate surface-wave discharges inside either cylindrical or coaxial structures. The neutral and ion wall flux is self-consistently estimated based on a simplified analytical description both for electropositive and electronegative plasmas. The simulation results are compared with experimental data from various discharge setups of either argon or oxygen, measured or obtained from the literature over a wide range of pressure and power, for a continuous and a pulse-modulated power input. A good agreement is observed between the simulations and the measurements. The contribution of the wall flux on the net loss rates is quantified for a variety of species in different discharge setups. A coaxial plasmaline is further investigated to reveal the detailed behaviour of plasma properties with respect to input power and pressure.